Digital consultation in primary healthcare: the effects on access, efficiency and patient safety based on provider experience; a qualitative study. (2nd October 2022) - Eriksson, Pär; Hammar, Tora; Lagrosen, Stefan; Nilsson, Evalill
Abstract: Objective: The objective of the study was to explore the experiences of healthcare staff working with and being part of the implementation of a digital platform for patient-provider consultation across quality dimensions of access, efficiency, and patient safety. Design: The study uses qualitative design to investigate experiences and the views of healthcare professionals. Data collection combined semi-structured individual and focus-group interviews. Content analysis was used to identify categories within the content areas 'access', 'efficiency', and 'patient safety'. Setting: The basis for the study was an e-consultation platform introduced in three primary healthcare centres in the County of Kalmar in southeast Sweden in 2019. Results: Healthcare staff experienced that the platform offered an open channel for communication with patients in need of frequent contact. This reduced anxiety and therefore the frequency of follow-up appointments. Healthcare staff also noted that the platform offered flexibility in contact benefitting patients with mental health problems. These patients were found to make contact through the platform after closing hours when problems were more acute or intense. However, the risk of digitally illiterate groups being excluded was also noted. Efficiency gains were identified among patients with simple cases which were handled more quickly through the platform. However, low uptake and the experience that the platform did not replace, rather was added on top of other already existing functions and procedures, negatively affected the overall efficiency. Standardized questions in automated medical history-taking contributed to patient safety. Conclusion: The findings suggest that text-based e-consultation platforms may bring important quality improvements to primary healthcare service in terms of access, efficiency, and patient safety. Yet, areas where e-consultation does not contribute to quality improvements puts important quality gains at risk. KEY POINTS: Text based digital consultation improved access for patients in need of frequent appointments and for patients with mental health problems. Efficiency gains among patients with simple cases, and in dealing with patients with mental health problems were noted. However, lack of confidence in platform functions due to low uptake, and limited control over work situation, were perceived as negatively affecting overall efficiency. Health care staff experienced improved patient safety through a standardized set of questions in automated medical history-taking.